EVALUASI PENERAPAN PEMOTONGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 23 PADA PT. BANK SYARIAH MANDIRI - Senduk, Claudia Yunike; Saerang, David P. E.; Nangoi, Grace B. (Universitas Sam Ratulangi, 2019)
Income Tax Article 23 (PPh Article 23) is a tax imposed on income on capital, service delivery, or gifts and awards, other than those that have been deducted by PPh Article 21. The research was conducted at the Mandiri Syariah Bank Manado Branch which is one of PT. BSM in North Sulawesi. The purpose of this study was to analyze the application of deductions, deposits and reporting of PPh 23 to the Manado Branch of Islamic Banks. The method used is descriptive analysis, where observations and interviews are conducted directly with the company that is the object of research. The results of the research conducted, Bank Syariah Mandiri has carried out its tax obligations properly and in accordance with the rules of procedure for deduction, deposit, and reporting applicable tax regulations in PPh 23 of Law No. 36 Of 2008. However, Bank Syariah Mandiri must continue to follow the development of existing tax regulations to avoid errors in the process of calculating, deducting, depositing, and reporting Article 23 of Income Tax.